Chlororespiration Controls Growth Under Intermittent Light. Issue 2 (29th November 2018) - Nawrocki, Wojciech J.; Buchert, Felix; Joliot, Pierre; Rappaport, Fabrice; Bailleul, Benjamin; Wollman, Francis-André
Abstract : Chlororespiration consumes photo-generated reductants in the green alga Chlamydomonas reinhardtii during periods without illumination, thus regulating the redox state of the chloroplast and preparing photosynthesis for the onset of light. Abstract: Whereas photosynthetic function under steady-state light conditions has been well characterized, little is known about its changes that occur in response to light fluctuations. Chlororespiration, a simplified respiratory chain, is widespread across all photosynthetic lineages, but its role remains elusive. Here, we show that chlororespiration plays a crucial role in intermittent-light conditions in the green alga Chlamydomonas reinhardtii . Chlororespiration, which is localized in thylakoid membranes together with the photosynthetic electron transfer chain, involves plastoquinone reduction and plastoquinol oxidation by a Plastid Terminal Oxidase (PTOX). We show that PTOX activity is critical for growth under intermittent light, with severe growth defects being observed in a mutant lacking PTOX2, the major plastoquinol oxidase. We demonstrate that the hampered growth results from a major change in the kinetics of redox relaxation of the photosynthetic electron transfer chain during the dark periods. This change, in turn, has a dramatic effect on the physiology of photosynthesis during the light periods, notably stimulating cyclic electron flow at the expense of the linear electron flow.